Delegacia Eletrônica: uma inovação da polícia civil do estado de São Paulo - Florencio, Patricia Fernandes de Souza (Universidade Federal de São Carlos, 2018)
The concept of the Electronic Government (e-gov) leads us to consider that the Information and communication technology (ICTs) are applied at various levels of government, especially the evolution of public services. The entrepreneurial State appropriates the theories of innovation and is a fundamental player in the development of society. The search for excellence in the provision service led to the creation of the Electronic Police Station by the Civil Police of the State of São Paulo. Seeking to contribute with the innovation studies in the public management. This work identifies solutions adopted to overcome of difficulties encountered in the implementation of this pioneer project in the State of São Paulo to serve as a reference for future developments, provide context within the models of public management, and address innovation paradigms. Through of qualitative research of exploratory character, the single case study was used by interviews and access to several documents. As a result, after the content analysis, we have the presentation typification of the object under the light of innovation, relating it with the management models and demonstrating the way of overcoming the barriers encountered.
Electronic Police Station: an innovation of the civil police of the state of São Paulo
Keywords: Boletim Eletrônico de Ocorrência; Inovação na administração pública; Governo Eletrônico; Electronic Bulletin of Occurrence; Public innovation; Electronic Government; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO::INSTITUICOES GOVERNAMENTAIS ESPECIFICAS